Design and Fabrication of a Wideband 8-Element Series-Feed Array on Metallic-Nanowire-Membrane Interposer for Millimeter Wave Frequency - Darweesh, Nawar [UNESP]; Bernardo, Helton; Ribeiro, Raul O. [UNESP]; Aldaya, Ivan [UNESP]; Santos, Renan A.; Da Rosa, Guilherme S. [UNESP]; Rehder, Gustavo P.; Serrano, Ariana L. C.; Penchel, Rafael A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The purpose of this work is to present an 8-element wideband series-fed array antenna fabricated on a metallic-nanowire-membrane (MnM) interposer for 60 GHz millimeter-wave applications. The MnM interposer, based on nanoporous technology filled with copper, serves as an novel substrate with high potential for 3D integrated circuits due to the ease of creating through-substrate vias (TSV) and interconnections between microwave components and system-on-chip (SoC). The results demonstrate a wideband frequency with adequate impedance matching of 19.48 GHz (simulated) and 23.80 GHz (measured).
Keywords: 3D integration; Millimeter-Wave (mmW); MnM interposer; series-fed array antennas